THE INFLUENCE OF IRANIAN SCHOLARSHIPS ON ISLAMIC EDUCATION IN KANO, 1979-2015 - Abdulaziz Mamuda; Salihu Zubairu Mustapha (International Studies Journal)
The 1979 Iranian revolution prepared ground for winning the hearts and minds of Muslims globally through various methods such as promotion of religious lectures and sponsoring religious education, establishment of Islamic schools, distribution of Islamic literature, and organizing of an Islamic conference abroad. This strategy was borne out of the new Iranian foreign policy, which is characterized by the promotion and exportation of the Iranian brand of Shiism, along with the political and religious doctrines that had been described as “Khomeinism” to other countries one of which is Nigeria. This situation paved way for many Kano indigenes to study in the best Iranian institutions of higher learning. This paper therefore examines the influence of the Iranian scholarships on Islamic education in Kano. It further argues that those who studied in Iran, after their return to Kano from Iran started constructing Islamiyya schools at various places in metropolitan Kano in order to reduce the growing popularity of not only Salafis, but also the Tijjaniyya and Qadiriyya Sufi Orders. Through the Fudiyyah schools, the Islamic Movement in Nigeria stands a better chance of attracting more patronage and legitimacy among Muslims in Kano, restricting their members from attending other schools and especially given the development of the group’s competitions with its Sunni rivals, the Fudiyyah schools served as check-mate to the similar Islamiyya school system operated by the Sunnis.